Silicon as an intermediary between renewable energy and hydrogen - Norbert Auner (Deutsche Bank Research, 2004)
Non-renewable energy sources are becoming depleted. Air and water (our environment) are precious and will be under increased jeopardy without effective energy and environmental policies. A hydrogen technology based upon solar energy represents a viable solution to these problems. Silicon successfully functions as a tailor-made intermediate linking decentrally operating renewable energy-generation technology with equally decentrally organised hydrogen-based infrastructure at any location of choice. The transport and storage of silicon are free from potential hazards and/or high energy losses and require a simple infrastructure similar to that needed for coal.
Keywords: 330; Regenerative Energie; Wasserstoff; Halbmetall; Dezentrale Energieversorgung